O papel da ética na formação do químico: um olhar no processo de formação inicial do licenciado na região oeste do Paraná - Lazzarin, Iara Lúcia (2015)
The present paper is about the study of ethics in chemistry graduation classes from two public universities, located in Paraná’s state western region. The chemistry classes’ syllabus establish, to the chemistry graduate, the pedagogic applications of the knowledge and experiences in the field of chemistry and alikes, in the professional acting as an educator in the national elementary education. So, the students’ initial formation is determinant to the development of skills that are required in the classroom. Therefore is necessary that beyond the specifics field subjects, there’s concomitantly discussions about topics like character, ethics and moral. This study has for its main purpose the analysis of the chemistry graduation classes’ coordinators, teachers and students understanding about the study and reflection about ethical principles that should be approached during the initial formation of the chemistry teachers. The present paper was written in a qualitative and quantitative research perspective, which the methodological course used was the documental research, which analyzed laws and basic guidelines of the chemistry discipline, the politic pedagogical projects and syllabus. The field research was done through interviews with the coordinators and teachers of the classes, and the students answered a questionnaire which contained open and closed questions. The results points to a small amount of hours destined to the ethics study in the analyzed classes and to a small reference to subjects that approach ethics in the classes’ syllabus. The results indicate also the necessity of implementing new structures to these courses, in a way that the insertion of subjects related to ethic are includes in the disciplines. Such attitude would allow to develop improve necessary skills to the reflection concerning the study of ethics on the students, aiming the preparation to act in the educational system that embraces responsibility, solidarity and citizenship aspects in the formation process of the new generations